2005
DOI: 10.1136/emj.2005.026575
|View full text |Cite
|
Sign up to set email alerts
|

Topical anaesthetic versus lidocaine infiltration to allow closure of skin wounds in children

Abstract: A short cut review was carried out to establish whether transthoracic ultrasound can be used to diagnose pneumothoraces in trauma patients. A total of 46 papers were found using the reported search, of which four represented the best evidence to answer the clinical question. The author, date and country of publication, patient group studied, study type, relevant outcomes, results, and study weaknesses of these best papers are tabulated. A clinical bottom line is stated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 11 publications
(9 reference statements)
0
22
0
2
Order By: Relevance
“…Our study showed a significant reduction in the number of children referred for general anaesthesia. The advantages of topical anaesthesia, while providing effective anaesthesia, include painless application, no needle and no tissue distortion, as occurs after subcutaneous infiltration of local anaesthetic [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study showed a significant reduction in the number of children referred for general anaesthesia. The advantages of topical anaesthesia, while providing effective anaesthesia, include painless application, no needle and no tissue distortion, as occurs after subcutaneous infiltration of local anaesthetic [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…As there is a large body of evidence in the literature showing how efficacious and safe LAT gel is for the repair of wounds [11][12][13][14][15], we believed that a randomized controlled trial was not warranted. We wanted all of our patients to benefit from the gel once it was introduced and decided to assess it retrospectively following this.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 The infiltration analgesia is made in concentrations of 1% to 5% as an aqueous solution of the hydrochloride, is applied intra-or subcutaneously, and spreads by diffusion in the tissue. 15,16 Two pharmacologic options are practiced to improve the local bioavailability of lidocaine in the tissue.…”
Section: Co-application Of Lidocaine and Haasementioning
confidence: 99%
“…4 Investigators have considered replacing infiltration entirely with topical anesthesia, brought about, for example, by tetracaine-adrenaline-cocaine-containing formulations and variants thereof. [5][6][7][8] Despite evidence of comparable efficacy, topical application of local anesthetics is still not common in the United Kingdom, possibly due to a perceived lack of efficacy, combined with the prolonged time required for effective anesthesia induction. 9,10 Effective topical anesthesia requires a particular delivery formulation.…”
mentioning
confidence: 99%